ASOSIASI ANTARA PERUBAHAN HARGA SAHAM DAN INVESTMENT OPPORTUNITY SET PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA - Indah Martati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
This research is aimed at examining the relationship between the actual Stock return toward the investment opportunity set (IOS) as the growth proxy of manufacturing companies which listing at Indonesian Stock Market. The IOS proxies used are market to book value of equity (MBVE), market to book value of assets (MBVA), price earning ratio (PER), Firm Value to book value of property, plant and equipment (VPPE), ratio capital expenditures to book value of asset (CEBVA), and ratio capital expenditures to market value of asset (CEMVA).The value of each indicators analysed by using common factor analysis. The normality data is tested by using one sample kolmogorov smirnov test continued with correlation test non parametric correlation model Kendall’s tau b. The purposive sampling is used in this research for ten years observation (1998 – 2007) with pool data method. The number of sample used is 240 manufacturing companies that listing at Indonesian Stock Market. The result of the research show that the direct and indirect correlation only occurs partially toward  market to book value of assets (MBVA) proxy. It indicates that there is direct and indirect positive relation through firm realized growth  and financing policy intervening variable but  it does not occur to the  composite IOS  proxies.